Cortactin: A major cellular target of the gastric carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Backert, Steffen; Tegtmeyer, Nicole (Cancers, 2020)
Cortactin is an actin binding protein and actin nucleation promoting factor regulating cytoskeletal rearrangements in nearly all eukaryotic cell types. From this perspective, cortactin poses an attractive target for pathogens to manipulate a given host cell to their own benefit. One of the pathogens following this strategy is Helicobacter pylori, which can cause a variety of gastric diseases and has been shown to be the major risk factor for the onset of gastric cancer. During infection of gastric epithelial cells, H. pylori hijacks the cellular kinase signaling pathways, leading to the disruption of key cell functions. Specifically, by overruling the phosphorylation status of cortactin, H. pylori alternates the activity of molecular interaction partners of this important protein, thereby manipulating the performance of actin-cytoskeletal rearrangements and cell movement. In addition, H. pylori utilizes a unique mechanism to activate focal adhesion kinase, which subsequently prevents host epithelial cells from extensive lifting from the extracellular matrix in order to achieve chronic infection in the human stomach.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Abl; CagA; CagPAI; FAK; Helicobacter pylori; SHP2; Signaling; Src; T4SS; Type IV secretion; Tyrosine kinases